Medieval horse stable; the results of multi proxy interdisciplinary research. - Miroslav Dejmal; Lenka Lisá; Miriam Fišáková Nývltová; Aleš Bajer; Libor Petr; Petr Kočár; Romana Kočárová; Ladislav Nejman; Michal Rybníček; Zdenka Sůvová; Randy Culp; Hanuš Vavrčík (PLoS ONE, 2014)
A multi proxy approach was applied in the reconstruction of the architecture of Medieval horse stable architecture, the maintenance practices associated with that structure as well as horse alimentation at the beginning of 13th century in Central Europe. Finally, an interpretation of the local vegetation structure along Morava River, Czech Republic is presented. The investigated stable experienced two construction phases. The infill was well preserved and its composition reflects maintenance practices. The uppermost part of the infill was composed of fresh stabling, which accumulated within a few months at the end of summer. Horses from different backgrounds were kept in the stable and this is reflected in the results of isotope analyses. Horses were fed meadow grasses as well as woody vegetation, millet, oat, and less commonly hemp, wheat and rye. Three possible explanations of stable usage are suggested. The stable was probably used on a temporary basis for horses of workers employed at the castle, courier horses and horses used in battle.